Rat models of postintracerebral hemorrhage pneumonia induced by nasal inoculation with Klebsiella pneumoniae or intratracheal inoculation with LPS - Wang, Ruihua; Gan, Changlian; Mao, Rui; Chen, Yang; Yan, Ru; Li, Geng; Xiong, Tianqin; Guo, Jianwen (Frontiers in Immunology, 2025)
BackgroundA stable and reproducible experimental bacterial pneumonia model postintracerebral hemorrhage (ICH) is necessary to help investigating the pathogenesis and novel treatments of Stroke-associated pneumonia (SAP).AimTo establish a Gram-negative bacterial pneumonia-complicating ICH rat model and an acute lung injury (ALI)-complicating ICH rat model.MethodsWe established two standardized models of post-ICH pneumonia by nasal inoculation with Klebsiella pneumoniae (Kp) or intratracheal inoculation with lipopolysaccharide (LPS). Survival and neurological scores were monitored. Magnetic resonance imaging was performed to evaluate hematoma volume. Abdominal aortic blood was collected for leukocyte counting, serum was isolated to determine concentrations of S100β and proinflammatory cytokines using ELISAs. Histopathological changes of brain, lung and gut were assessed using hematoxylin−eosin staining. Lung was isolated for immunofluorescence staining for myeloperoxidase (MPO). Bronchoalveolar lavage fluid was collected for leukocyte counting, and supernatant was prepared to measure MPO activity. Ileum was isolated for immunofluorescence staining for tight junction proteins ZO-1 and γδ TCRs/IL-17A and for Alcian blue–nuclear fast red staining of acidic mucins. Feces were collected, 16S rRNA sequencing, untargeted metabolomics and Spearman’s correlation analyses were performed to explore changes of gut microbiota, metabolites and their interactions.ResultsIn Kp-induced bacterial pneumonia-complicating ICH rats, we demonstrated that Kp challenge caused more severe neurological deficits, brain damage, neuroinflammation, and aggravated pneumonia and lung injury. Disruptions of the intestinal structure and gut barrier and the reductions of the protective intestinal IL-17A-producing γδT cells were also observed. Kp challenge exacerbated the gut microbiota dysbiosis and fecal metabolic profile disorders, which were characterized by abnormal sphingolipid metabolism especially elevated ceramide levels; increased levels of neurotoxic quinolinic acid and an upregulation of tryptophan (Trp)–serotonin–melatonin pathway. Spearman’s correlation analyses further revealed that the reduction or depletion of some beneficial bacteria, such as Allobaculum and Faecalitalea, and the blooming of some opportunistic pathogens, such as Turicibacter, Dietzia, Corynebacterium and Clostridium_sensu_stricto_1 in Kp-induced SAP rats were associated with the disordered sphingolipid and Trp metabolism. Using an LPS-induced ALI complicating ICH model, we also characterized SAP-induced brain, lung and gut histopathology injuries; peripheral immune disorders and intense pulmonary inflammatory responses.ConclusionsThese two models may be highly useful for investigating the pathogenesis and screening and optimizing potential treatments for SAP. Moreover, the differential genera and sphingolipid or Trp metabolites identified above seem to be promising therapeutic targets.